Discovery Learning Model and Props of Statistical Kenik In Improving The Mathematical Communication Ability of Junior High School Students - Gustiani, Dini Sri; Irman, Ade; Fadhillah, Fika Muji (IKIP Siliwangi, 2019)
The purpose of this study is to examine the achievement and improvement of junior high school students' mathematical communication ability using discovery learning models and props of statistical kenik compared to students who use ordinary learning, and student activities during learning using discovery learning models and props of statistical kenik to take place. This study used a quasi-experimental design. The experimental group obtained learning with discovery learning models and props of statistical kenik and control groups obtained regular learning. The instrument used was a test of mathematical communication ability. The population in this study were all eighth grade students of SMP Negeri 2 Cilamaya Kulon Karawang. With the sample subjects were eighth grade students as many as two classes from the five existing classes randomly selected. The results of this study are: (1) There is achievement and improvement of mathematical communication ability between students whose learning uses discovery learning models and props of statistical kenik compared to students who use ordinary learning; (2) Learning by using discovery learning models and visual aids shows that the learning process is more effective in mathematical problems solving and students can find statistical material concepts.